Zinc(II) iodide-firected β-mannosylation: reaction selectivity, mode, and application - Zhong, Xuemei (2022)
A direct, efficient, and versatile glycosylation methodology promises the systematic synthesis of oligosaccharides and glycoconjugates in a streamlined fashion like the synthesis of medium to long-chain nucleotides and peptides. The development of a generally applicable approach for the construction of 1,2-cis-glycosidic bond with controlled stereoselectivity remains a major challenge, especially for the synthesis of β-mannosides. Here, we report a direct mannosylation strategy mediated by ZnI2, a mild Lewis acid, for the highly stereoselective construction of 1,2-cis-β linkages employing easily accessible 4,6-O-tethered mannosyl trichloroacetimidate donors. The versatility and effectiveness of this strategy were demonstrated with successful β-mannosylation of a wide variety of alcohol acceptors, including complex natural products, amino acids, and glycosides. Through iteratively performing ZnI2-mediated mannosylation with the chitobiosyl azide acceptor followed by site-selective deprotection of the mannosylation product, the novel methodology enables the modular synthesis of the key intermediate trisaccharide with Man-β-(1 → 4)-GlcNAc-β-(1 → 4)-GlcNAc linkage for N-glycan synthesis. Theoretical investigations with density functional theory calculations delved into the mechanistic details of this β-selective mannosylation and elucidated two zinc cations' essential roles as the activating agent of the donor and the principal mediator of the cis-directing intermolecular interaction.